Anatomi Jaringan Kayu Terserang Penyakit Lapuk Kayu Teras - Nuhamara, Simon Taka; Hadi, Soetrisno (Institut Pertanian Bogor (IPB University), 1999)
A study was undertaken to determine the anatomical structures of decaying heartwood in the stem part of Acacia mangium Willd where the branch stubs were found. Sections of the decaying heartwood were made and the microscopical features were recorded. Compartmentalization of the decaying heartwood was observed and the walls of the compartment is characterized by the discoloration of the wood tissues suspected to be associated with the blocking of the vessels and pits, formation of tylosis, deposition of gum, and formation of axial parenchyma. The branch stub on the stem is known to be the entry point for different microorganisms leading to the heart-rot development by heartwood decaying fungi.